Analisa Perbandingan Metode Scrum dan Metode Waterfall: Analisa Perbandingan Metode Scrum dan Metode Waterfall - Sangadji, Yunita; Dwi Wahyuni, Evi; Nurul Ramadha, Firdatul; Salsabila Shafiyyah Fitriyani, Annisaa (Jurnal Media Informatika dan Teknologi, 2024)
Abstract In software development, the project management method employed has a significant impact on the final outcome and the efficiency of the process. The most prevalent methods in software development are Scrum and waterfall. Each method possesses distinctive advantages and disadvantages. The Scrum method is renowned for its flexibility in organizing changes as the software development process progresses. In contrast, the waterfall method employs a linear and structured approach to software development. The methodology employed in this research entails a qualitative approach to gain a deeper understanding of the Scrum and waterfall methods through a literature review and comparative analysis. Through the literature review and comparative analysis conducted, the author can explore more profound insights into the implementation and effectiveness of the Scrum and waterfall methods. The findings of this research indicate that the selection of an appropriate software development methodology should be based on the specific characteristics of the project in question, the needs of the users, the capabilities of the development team, and an evaluation of the advantages and disadvantages of each method. Keywords—Software, Scrum, Waterfal